Focusing on frailty: Applying a person-centered, integrated approach to a multidimensional condition - Bobrowicz-Campos, E.; Apóstolo, J. (JBI Evidence Synthesis, 2020)
In light of the growing need to increase sustainability and efficiency of health and social care systems, strengthening the person-centered and integrated approach in geriatric care is essential. This approach may contribute to the prevention of age-related dependency and subsequently allow better management of human and material resources allocated in health.